Meteorological influences on solar energy production in a coastal Amazon region - Freitas, Marcos Aurélio Alves; Rodrigues, Leonardo Henrique de Sá; Sousa, Luan Victor Pereira de; Aguiar, Pedro Henrique Modesto de; Ferreira, Ana Roberta Barros; Silva, Fabricio Brito (Ciência e Natura, 2022)
A study was conducted with a photovoltaic distributed generation system in São Luís, Brazil, to determine the influence of meteorological variables on the generation of energy. The methodology is composed of three stages: the first corresponds to the obtaining, organization, and treatment of the data; the second involves the application of mathematical models to determine the yield, operating temperature, nominal power, and estimated power; and the third is to generate the correlations obtained between the monitored climatic variables, whether on an hourly, daily, monthly, or annual scale. For an average temperature of 27.50ºC in March, it was verified that the ultraviolet radiation was 5.06, while the average of the total radiation was 481.01 W.m-2. The maximum peak temperature was 27.88°C at noon, while the ultraviolet radiation was 8.55 and total radiation was 794.97 W.m-2. At this average temperature variation of 0.38°C, there is a variation of 313.96 W.m-2. It is concluded that, because São Luís is very close to the equator, the conditions to produce the system are favorable, mainly because, on average, there were no abrupt changes in temperature and radiation for the period studied. Even in the wintry period, the production behaved within the parameters designed.